1999
DOI: 10.1111/j.1469-7793.1999.t01-1-00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‐1 modulates the activity of the volume‐regulated chloride channel

Abstract: Caveolae are Ù-shaped invaginations of the plasma membrane with a diameter of 50-100 nm that are present in many different cell types (Anderson, 1998). Caveolae form discrete lipid microdomains within the plasma membrane due to the preferential packing of sphingolipids and cholesterol. The principal protein component of caveolae is caveolin, a 21-24 kDa membrane protein that inserts into the caveolar membrane via an intramembrane hairpin loop. Four different isoforms encoded by three genes have been described:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
74
3
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 25 publications
10
74
3
1
Order By: Relevance
“…This activity was blocked by the addition of RU486, indicating that upregulation of caveolin-1 by MPA is mediated by the classical PR. Similar experiments were conducted in human breast cancer T47D cells which do not express caveolin-1, as shown by others (Trouet et al, 1999) and by our own experiments (data not shown). On T47D cells, progesterone has biphasic effects: stimulating growth first (0-24 h) and then inhibiting it (24-48 h) (Lange et al, 1999).…”
Section: Resultssupporting
confidence: 87%
“…This activity was blocked by the addition of RU486, indicating that upregulation of caveolin-1 by MPA is mediated by the classical PR. Similar experiments were conducted in human breast cancer T47D cells which do not express caveolin-1, as shown by others (Trouet et al, 1999) and by our own experiments (data not shown). On T47D cells, progesterone has biphasic effects: stimulating growth first (0-24 h) and then inhibiting it (24-48 h) (Lange et al, 1999).…”
Section: Resultssupporting
confidence: 87%
“…The association of previously separate proteins that might then be able to activate ion channels could also be important. Consistent with this novel ' occluded anion channel ' hypothesis are the observations that caveolins modulate volume-regulated anion channel activity [54] and that caveolae cluster centrally in cells exposed to hyperosmotic medium, provided that the actin and microtubule cytoskeletons both remain intact [55].…”
Section: Possible Cellular Roles For Clic4supporting
confidence: 59%
“…This, on the other hand, seems in contrast to the recent proposal that VRAC activation is dependent on the integrity of caveolae (63), and that caveolin-1 may increase VRAC availability in the plasma membrane and/or be involved in the signaling events leading to VRAC activation (64).…”
contrasting
confidence: 51%
“…RhoA and Rho kinase exhibit activity-dependent translocation to caveolae (62,65), suggesting a role for cholesterol depletion-induced changes in caveolae organization. Interestingly, caveolae are also sensitive to cell volume perturbations (46), and have been implicated in VRAC regulation (63,64). On the other hand, preliminary studies revealed no detectable changes in caveolin-1 distribution in cholesterol-depleted ELA cells (S. F. Pedersen, T. Kjaer Klausen, and E. K. Hoffmann, unpublished observations).…”
Section: Discussionmentioning
confidence: 97%